Progress in Flight Physics 2013
DOI: 10.1051/eucass/201305621
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic model development and simulation of airliner spin for upset recovery

Abstract: The aerodynamic model of a generic airliner con¦guration is developed for a wide range of angles of attack, sideslip and angular rate based on experimental data obtained in wind tunnels using static, forced oscillations and rotary balance tests. The developed aerodynamic model is applied for the investigation of the airliner scaled model nonlinear dynamics at high angles of attack with an intensive rotation to identify potential spin modes and spin recovery procedures. The evaluated equilibrium spin parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The European research project SUPRA (Simulation of Upset Recovery in Aviation) expanded the flight simulation envelope, by developing an extended aerodynamic model, as well as novel motion cueing strategies. The SUPRA-extended aerodynamic model is built onto a data package representing a generic transport aircraft, and reproduces the typical behavior of a transport aircraft at high angles of attack (AoA) and sideslip [7,8]. It captures the longitudinal and lateral instabilities, and degraded controllability.…”
Section: Description Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The European research project SUPRA (Simulation of Upset Recovery in Aviation) expanded the flight simulation envelope, by developing an extended aerodynamic model, as well as novel motion cueing strategies. The SUPRA-extended aerodynamic model is built onto a data package representing a generic transport aircraft, and reproduces the typical behavior of a transport aircraft at high angles of attack (AoA) and sideslip [7,8]. It captures the longitudinal and lateral instabilities, and degraded controllability.…”
Section: Description Of Workmentioning
confidence: 99%
“…It captures the longitudinal and lateral instabilities, and degraded controllability. Its adjustable parameters allow for simulating various types of departures, as described in previous papers [7,8].…”
Section: Description Of Workmentioning
confidence: 99%
“…Considerable efforts have, therefore, been put in by various countries in design and development of dynamic wind tunnel test facilities like rotary balance apparatus, forced oscillation motion rigs, oscillatory coning motion rigs, etc., that can emulate aircraft motion in post stall maneuvers (Bergmann, 2009;Jin et al, 2015;Zhang et al, 2015). Aerodynamic data from such dynamic wind tunnel test setups has been used effectively in identifying aircraft steady spin modes and simulation of post stall maneuvers (Bihrle, 1990;Murch and Foster, 2007;Khrabrov et al, 2013;Paul and Gopalarathnam, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Colgan Air 3407 and Air France Flight 447 accidents 1,2 that occurred in February and June 2009, respectively, highlighted deficiencies in pilot training with respect to recovering the aircraft from stall and upset states. Furthermore, a recently-concluded 16 year study by Calspan, 3 funded mainly by NASA, the Federal Aviation Administration (FAA), and the United States Navy, concluded that pilots were ill-equipped and untrained to recognize an aircraft in an upset state and then perform any appropriate control inputs to successfully recover from this state.…”
Section: Introductionmentioning
confidence: 99%
“…At present, research is being conducted into the improvement of commercial transport aircraft flight modeling and control through the NASA Aviation Safety and Security Program (AvSSP) [7][8][9][10][11] and the European Union Simulation and Upset Recovery in Aviation project. [12][13][14][15][16] The importance attached to commercial transport aircraft is understandable given that passenger safety is of the utmost importance to the transportation industry. However, according to the Aircraft Owners and Pilots Association Air Safety Institute 2010 Nall Report, 17 for fixed wing aircraft over the past decade, the average accident rate was 67% higher for non-commercial flights and the rate of fatal accidents was 120% higher in comparison with commercial flights.…”
Section: Introductionmentioning
confidence: 99%